Disorders of Calcium-Phosphorus Metabolism in Children with Chronic Pyelonephritis (Texas Journal of Medical Science, 2022)
The connection between the condition of the oral cavity and general somatic diseases is constantly emphasized by dentists. This arouses the constant interest of researchers to study the features of the course of dental pathology against the background of some forms of somatic diseases. In the literature, there is information about the condition of the hard tissues of the teeth, periodontal tissues and the mucous membrane of the oral cavity in children with chronic pyelonephritis. Morphological association of pathological processes in children with chronic pyelonephritis is manifested by kidney and periodontal tissues, lymphocytic infiltration, fibrosis, damage to microvascular vessels. With the development of chronic pyelonephritis, structural and functional changes in periodontal tissues become dystrophic, accompanied by vasoconstriction of microvessels and tissue sclerosis